Optimising targeted antibodies for the treatment of metastatic solid tumours - Herbertson, Rebecca A. (2009)
This thesis describes three different strategies employed with the aim of optimising targeted antibodies for the treatment of metastatic solid tumours. Whilst the search for improved predictors of response to anti-EGFR antibodies continues, paired primary and metastatic archived tissue from 32 patients with metastatic colorectal cancer was explored for the immunohistochemical expression of EGFR, pEGFR and pMAPK and activating mutations in KRAS, BRAF and PI3KCA. The resulting discordance between expression of pEGFR and pMAPK between primary and metastatic tissue CRC suggests they are unlikely to be useful biomarkers for response unless metastatic tissue is also analysed. Confirmation that mutations in KRAS, BRAF and PI3KCA are concordant in primary and metastatic tissue supports the analysis of archived primary tissue alone for mutation screening. PI3KCA mutations were shown to be present in patients with both wild-type and mutant KRAS, which provides both an additional method for resistance in wild type tumours and a mechanism for high resistance in those with mutant primary tumours, suggesting screening patients for all 3 mutations should be encouraged for future trials of anti-EGFR antibodies.